2020
DOI: 10.3390/cryst10040288
|View full text |Cite|
|
Sign up to set email alerts
|

Two- and Three-Dimensional Superconducting Phases in the Weyl Semimetal TaP at Ambient Pressure

Abstract: The motivation to search for signatures of superconductivity in Weyl semi-metals and other topological phases lies in their potential for hosting exotic phenomena such as nonzero-momentum pairing or the Majorana fermion, a viable candidate for the ultimate realization of a scalable quantum computer. Until now, however, all known reports of superconductivity in type-I Weyl semi-metals have arisen through surface contact with a sharp tip, focused ion-beam surface treatment or the application of high pressures. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…At low temperatures around 3 K, a drop in resistance signals a superconducting transition. As WP 2 in bulk form is not superconducting, this likely arises from an amorphous W-rich surface layer due to the FIB fabrication similar to observations made in NbAs 33 and TaP 34 . In Fig.…”
Section: Resultssupporting
confidence: 54%
“…At low temperatures around 3 K, a drop in resistance signals a superconducting transition. As WP 2 in bulk form is not superconducting, this likely arises from an amorphous W-rich surface layer due to the FIB fabrication similar to observations made in NbAs 33 and TaP 34 . In Fig.…”
Section: Resultssupporting
confidence: 54%
“…It was shown that the second‐order susceptibility of tantalum arsenide (TaAs) is two orders of magnitude larger than for high refractive index non‐centrosymmetric dielectrics, [ 18 ] an efficient nonlinear (NL) photocurrent generation was also demonstrated, [ 19 ] the near infrared glass‐coefficient was found to be the strongest so far reported [ 20 ] and efficient catalytic activity was observed for the hydrogen evolution reaction. [ 21 ] So far, experimental reports were limited to bulk [ 22,23 ] or micro structuring of the bulk crystal, [ 8,10,20 ] representing a natural restriction to the development of on‐chip applications.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, and excluding the case of effective 2D layered superconductors 58,59 , the flake is five times thicker than any superconducting films exhibiting a BKT transition reported so far 60 , making PtBi 2 a prime candidate to study low dimensional superconductivity. Among the few Weyl semimetals showing a superconducting transition under ambiant pressure [61][62][63][64][65] , PtBi 2 is, together with MoTe 2 66 , the only one exhibiting such a 2D superconductivity.…”
Section: Wuppertal Germanymentioning
confidence: 99%